Maxillary Sinus Augmentation Using Ceramic Alloplastic Granules or Paste: An Experimental Study in Rabbits - Michael Medeiros Costa; Daniele Botticelli; Ofer Moses; Yuki Omori; Shigeo Fujiwara; Erick Ricardo Silva; Samuel Porfirio Xavier (MDPI AG, 2021)
Background: Due to the lack of data comparing the biological behavior of two formulations, granules and paste, of alloplastic graft from microtomographic and histomorphometric points of view, the aim of the present experiment was to compare the histomorphometric and microtomographic healing of two formulations, i.e., granules (MR sites) or paste (MR-inject sites) of an alloplastic graft composed of a combination of beta-tricalcium phosphate and hydroxyapatite used for maxillary sinus lifting. Methods: A sinus lifting procedure was carried out bilaterally in 20 rabbits, and the elevated space was filled with either paste or granules of an alloplastic material. A collagen membrane was placed on the antrostomy and the animals were euthanized after 2 or 10 weeks, 10 animals each group. Microtomographic and histological analyses were performed. Results: Higher proportions of new bone formation were found at the MR, compared to the MR-inject sites both after 2 weeks (2.65 ± 2.89% vs. 0.08 ± 0.12%; p < 0.01) and 10 weeks of healing (34.20 ± 13.86 vs. 23.28 ± 10.35%; p = 0.022). Conclusions: It was concluded that new bone formation was faster in the MR sites, compared to the MR-inject. However, a longer time of healing should be allowed to make final conclusions about the efficiency in bone formation of the paste formulation of the biomaterial used in the present study.